Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Mekar Swalayan Kediri - Awfriellinka Pramesty; Edwin Agus Buniarto; Diana Ambarwati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to explain and prove the hypothesis regarding the influence of leadership style and organizational culture on employee performance through job satisfaction as an intervening variable at Mekar Swalayan Kediri. This type of research uses descriptive research with quantitative methods with sampling techniques, namely saturated sampling techniques where the population is 64 employees. The data analysis method used in this research is Partial Least Square (PLS) processed using the Smart PLS 3.0 program. The research results show that Leadership Style and Organizational culture (X2) have a significant effect on employee performance. Leadership style and organizational culture (X2) have a significant effect on job satisfaction. Organizational culture and job satisfaction have a significant effect on employee performance. Leadership style has a significant effect on employee performance through the job satisfaction variable. Organizational culture has a significant effect on employee performance through job satisfaction.